2020
DOI: 10.46365/jmio.v1i02.381
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Partikel Dan Variasi Komposisi Briket Pada Campuran Limbah Arang Kayu Alaban Dengan Sekam Padi Terhadap Karakteristik Briket Dan Pembakaran

Abstract: Fossil fuel energy is getting thinner every year, which raises concerns in the society over the energy crisis. For this reason, there is a need for innovations, namely better alternative energy. Alternative energy that can be utilized is wood waste from alaban wood and rice husk waste. This study aims to determine the characteristics of briquettes and combustion from a mixture of alaban wood charcoal waste and rice husk. This study uses variations in particle size of 40, 50, 60 mesh and a mixture of 70%:30%, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
1
0
3
Order By: Relevance
“…The average value of the volatile matter content in the cornstarch adhesive and rice flour is not much different, this is due to the organic compounds contained in the flour adhesive. Starch content affects the level of volatile matter [35], where the higher the starch content contained in a type of adhesive, the more volatile matter will be produced. In line with the results of this study which showed that the volatile matter content in rice flour had a slightly higher value (31.70%) when compared to cornstarch adhesive (30.90%).…”
Section: B Water Contentmentioning
confidence: 99%
“…The average value of the volatile matter content in the cornstarch adhesive and rice flour is not much different, this is due to the organic compounds contained in the flour adhesive. Starch content affects the level of volatile matter [35], where the higher the starch content contained in a type of adhesive, the more volatile matter will be produced. In line with the results of this study which showed that the volatile matter content in rice flour had a slightly higher value (31.70%) when compared to cornstarch adhesive (30.90%).…”
Section: B Water Contentmentioning
confidence: 99%
“…Perekat memiliki peran dalam laju pembakaran briket, semakin banyak perekat yang ditambahkan ke dalam briket, maka akan menurunkan laju pembakaran briket. Hal ini dikarenakan perekat menyebabkan butir-butir briket saling menempel kuat dan memperkecil pori-pori briket, membuat sulitnya udara luar masuk untuk mempercepat proses pembakaran briket [12].…”
Section: Laju Pembakaranunclassified
“…Selain ukuran partikel, perbandingan komposisi juga memberikan pengaruh terhadap kualitas briket. Menurut (Muhammad, 2017) variasi penambahan plastik yang semakin bertambah dapat berpengaruh terhadap hasil uji proksimat yang sebagai penentu kualitas briket dan hal yang sama juga disimpulkan bahwa variasi komposisi mempengaruhi karakteristik briket (Syarief et al, 1995).…”
Section: Pendahuluanunclassified
“…Volume limbah plastik ini akan terus bertambah seiring bertambahnya jumlah penduduk serta penggunaan plastik oleh industri makanan. Jenis plastik yang terbanyak digunakan adalah Polypropylene yaitu sebanyak 30,19% (Widiyatmoko et al, 2014). Hal ini karena polypropylene banyak digunakan untuk kemasan makanan, minuman dan memiliki daya regang yang tinggi Jumlah yang besar dan memiliki sifat yang mudah terbakar dapat dimanfaatkan menjadi bahan baku energi alternatif (Sahwan et al, 2005).…”
Section: Pendahuluanunclassified